2015
DOI: 10.6018/analesps.31.2.171721
|View full text |Cite
|
Sign up to set email alerts
|

Clima y satisfacción laboral en el contexto universitario

Abstract: Resumen: El objetivo del estudio es comprobar la relación del clima y la satisfacción laboral en el contexto de una universidad pública. Los datos fueron recogidos de 318 empleados públicos del personal de administración y servicios. Se realizaron análisis multinivel para comprobar los efectos transnivel del clima, operacionalizado a nivel de las áreas administrativas, y la satisfacción laboral individual. El modelo de Kopelman, Brief y Guzzo (1990) sirve de marco teórico para mostrar las relaciones entre el c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 86 publications
1
7
0
7
Order By: Relevance
“…In this study, climate showed a significant and positive reciprocal influence on job satisfaction (0.746), confirming the motivational process of the JD-R model. Furthermore, previous studies showed that when employees perceive their organisational climate in a more positive way, they are more satisfied [31]. Also, we found that role stress and burnout are significantly and positively related (0.953).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In this study, climate showed a significant and positive reciprocal influence on job satisfaction (0.746), confirming the motivational process of the JD-R model. Furthermore, previous studies showed that when employees perceive their organisational climate in a more positive way, they are more satisfied [31]. Also, we found that role stress and burnout are significantly and positively related (0.953).…”
Section: Discussionsupporting
confidence: 70%
“…Job resources seem to play a motivating role, fostering the learning, growth, and development of employees. Numerous studies have confirmed that the more positively employees perceive the organisational climate, the more satisfied they are [31].…”
Section: Introductionmentioning
confidence: 99%
“…Interest in the field of study of job insecurity has grown constantly, as flexible and changing labour relations have become an intrinsic element of the current labour market. It is assumed that job insecurity is not a transitory solution to adapt to a service-based economy, but rather that this way of organizing work is already a structural element (Crespo, Prieto Rodríguez, & Serrano Pascual, 2009), with important consequences for the well-being of workers (López-Araújo & Segovia, 2010;Pecino-Medina, Mañas-Rodriguez, Díaz-Fúnez, López-Puga, & Llopis-Marín, 2015;Serrano Rosa, Moya Albiol, & Salvador, 2009). This same approach proposed by Crespo and collaborators coincides with the approach defined by many authors, in different manners, over the last few years.…”
Section: The Perceived Job Insecurity Conceptmentioning
confidence: 99%
“…Uno de los indicadores más relevantes estudiados en el contexto laboral en trabajadores con discapacidad es la satisfacción laboral. Este constructo ha sido definido por diferentes autores como la respuesta evaluativa, afectiva y conductual hacia el trabajo que se desempeña (Pecino-Medina et al, 2015;Veloso-Besio et al, 2015).…”
Section: Introductionunclassified